2017
DOI: 10.1126/sciadv.aao1497
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent ions induce lateral structural inhomogeneities in polyelectrolyte brushes

Abstract: Polymer chain bridging by multivalent ions and solvophobic attractions drives structure formation in charged polymer brushes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
111
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(119 citation statements)
references
References 49 publications
7
111
1
Order By: Relevance
“…Depending on the chain stiffness, brush condensates adopt diverse morphological patterns that vary from semi-spherical octopus-like micelle domains to cylindrical bundles of rigid chains which protrude from the grafting surface. It was shown that when the grafting density is in a proper range, multivalent counterions can collapse flexible PE brush even in good solvent into octopus-like surface micelles displaying substantial lateral heterogeneity [42][43][44] , which has recently been confirmed experimentally for polystyrene sulfonate brush condensates in Y(NO 3 ) 3 solution 45 .…”
Section: Introductionmentioning
confidence: 81%
“…Depending on the chain stiffness, brush condensates adopt diverse morphological patterns that vary from semi-spherical octopus-like micelle domains to cylindrical bundles of rigid chains which protrude from the grafting surface. It was shown that when the grafting density is in a proper range, multivalent counterions can collapse flexible PE brush even in good solvent into octopus-like surface micelles displaying substantial lateral heterogeneity [42][43][44] , which has recently been confirmed experimentally for polystyrene sulfonate brush condensates in Y(NO 3 ) 3 solution 45 .…”
Section: Introductionmentioning
confidence: 81%
“…The collapse of polyelectrolyte brushes is largely caused by multivalent‐ion‐mediated interchain crosslinks . Both divalent and trivalent counterions can cause the collapse of polyelectrolyte brushes, but divalent ions show high ion specificity .…”
Section: Sfa Measurements On Polyelectrolyte Brushesmentioning
confidence: 99%
“…In contrast, a low concentration of Y 3+ ions (cf. Figure ) causes the collapse of the brush into a heterogeneous film, with apparent aggregation ascribed to the bridging of different chains by the multivalent ions …”
Section: Afm Measurements On Polyelectrolyte Brushesmentioning
confidence: 99%
See 2 more Smart Citations